Auditory neglect. Issue 5 (May 1989) - De Renzi, E; Gentilini, M; Barbieri, C
Abstract : Auditory neglect was investigated in normal controls and in patients with a recent unilateral hemispheric lesion, by requiring them to detect the interruptions that occurred in one ear in a sound delivered through earphones either mono-aurally or binaurally. Control patients accurately detected interruptions. One left brain damaged (LBD) patient missed only once in the ipsilateral ear while seven of the 30 right brain damaged (RBD) patients missed more than one signal in the monoaural test and nine patients did the same in the binaural test. Omissions were always more marked in the left ear and in the binaural test with a significant ear by test interaction. The lesion of these patients was in the parietal lobe (five patients) and the thalamus (four patients). The relation of auditory neglect to auditory extinction was investigated and found to be equivocal, in that there were seven RBD patients who showed extinction, but not neglect and, more importantly, two patients who exhibited the opposite pattern, thus challenging the view that extinction is a minor form of neglect. Also visual and auditory neglect were not consistently correlated, the former being present in nine RBD patients without auditory neglect and the latter in two RBD patients without visual neglect. The finding that in some RBD patients with auditory neglect omissions also occurred, though with less frequency, in the right ear, points to a right hemisphere participation in the deployment of attention not only to the contralateral, but also to the ipsilateral space.